“THE ROLE OF CITIZENS' SELF-GOVERNMENT BODIES AS A NATIONAL DEMOCRATIC INSTITUTION” (Scientific journal of the Fergana State University, 2024)
The article notes that the reforms and positive changes in self-governance in Uzbekistan in recent years have rapidly penetrated into all spheres of life, the importance of the "Safe Neighbourhood" system in the structure of self-governance, the advantages of the "Neighbourhood" operating system in the implementation of the "Safe Neighbourhood" system, provides information on the study of the concept of "safe neighbourhood" to prevent crime in neighbourhoods. Methods of comparative-critical study, analysis of political, pedagogical literature in research methods were used.As a result of the study, proposals were made for the implementation of the “Safe Neighborhood” system in the neighborhoods of our country.